Simulation of firebrands transport generated by the seat of fire - Matvienko, Oleg V. (Proceedings of SPIE)
Physical and mathematical model of the seat of fire, taking into account the transport of firebrands from the combustion zone was developed. The results received in the study are tentative and can be used only for a qualitative description of the process. The motion of firebrands is mainly determined by the aerodynamic processes accompanying the combustion process. At the initial stage of the motion the medium and large size firebrands are transported by the rising flow in the direction to the upper boundary of the thermal column, then are trapped by a toroidal vortex and are transported from the combustion zone to the external boundary of the circulating flow, where they are deposited on the underlying surface. The maximum rise height of the particles transported from the peripheral area is smaller, and the transport range is greater compared to the particles transported from the central area. Large firebrands have a small specific surface area (the ratio between the particle surface area and volume) compared to small firebrands. As a result, the temperature of large firebrands during landing is above the critical one in contrast to small firebrands, which may initiate the ignition of the underlying surface and the formation of the secondary seat of fire. © (2015) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.